Pengembangan Bahasa Sumbawa Standard melalui Penawaran Konsep Tata Aksara Bahasa Sumbawa (Lingua, 2019)
This paper aims to explain the literacy system in Sumbawa (BS), which includes the sound system (phoneme); grapheme system (letter); and phoneme distribution. Methodologically, data collection uses skilled methods, see (using written data), and introspection. The collected data was analyzed using intralingual method. The results showed that there were 29 phonemes in the BS, ie 10 vowels (/ i /, / I /, / u /, / e /, / E /, / ě /, / o /, / ò /, / a /, and / A /) and 19 consonants (/ p /, / b /, / t /, / d /, / c /, / j /, / k /, / g /, / q /, / s /, / /, / r /, / l /, / w /, and / y /).hh /, / m /, / n /, / ñ /, / The ten vowel phonemes are written with 6 letters (graphemes), namely i (representing / i / and / I /), u, e (representing / e / and / E /), ě, o, ò, and a (representing / a / and / A /). As for the 19 consonant phonemes each written with letters a number of existing phonemes. The vowel sound of BS can occupy the initial, middle, and final position of the word, except / e / (as [e]) can not occupy the final position, while / u / never appears in the ultima syllabe which ends with consonant. As for, consonant sounds can occupy the initial, middle, and final position of the word, except b, w, d, ny, j, g, h, and y can only occupy the initial and middle position, while q never occupy the starting position.